Genetic Analysis of 305-Day Milk Yield in Mehsana Buffaloes of Banaskantha and Mehsana Districts of Gujarat - Patel, Janvi J; Gajjar, Swapnil; Nayee, Nilesh; Joshi, Rajesh S; Patel, Ashish C; Patel, Mayank R; Ahlawat, Anshu R (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Buffaloes play a vital role in Indian dairy economy, contributing more than half of the nation’s total milk production. Among indigenous breeds, the Mehsana buffalo is a high-performing dual-purpose breed predominantly found in Gujarat. The present study was aimed to estimate the genetic parameters and evaluate the 305-day milk yield (305DMY) of Mehsana buffaloes maintained under field conditions in Mehsana and Banaskantha districts. A total of 18,888 buffaloes (15,418 from Mehsana and 3,470 from Banaskantha) with 305DMY records were analyzed using data retrieved from the NDDB’s INAPH–MIS (Information Network for Animal Productivity and Health - Management Information System) database. The mean 305DMY was 1962.75 ± 3.19 kg. Fixed effects, such as tehsil, year-season of calving, and age at calving significantly influenced milk yield, highlighting the role of environmental and management factors. Genetic variance was higher in Mehsana district (58,181) compared to Banaskantha (10,015), indicating greater genetic variability. Heritability of 305DMY was moderate in Mehsana (0.36) but appeared low in Banaskantha (0.051) mainly because of very high residual variation using BLUP model. Field data indicate that Banas animals show higher variability than Mehsana. This suggests that pedigree and phenotypic records alone are not sufficient to capture the true genetic variability, which results in underestimated heritability. Therefore, combining data from both Banaskantha and Mehsana for joint evaluation may improve genetic linkage and comparability between herds and lead to more accurate breeding value estimation. Using Random Regression Model (RRM), the overall heritability estimates were 0.2611 for Mehsana and 0.1436 for Banas buffaloes. The heritability estimate was observed as higher using random regression model than routine 305DMY BLUP model.